Vivre aux ixe-xie siècles sur le promontoire de Gien (Loiret) : architecture, activités et environnement d’un habitat privilégié - Mélinda Bizri; Quentin Borderie; Gaëtan Jouanin; Yannick Mazeau; Coline Lejault; Guillaume Saint-Didier; Sabrina Save; Alys Vaughan-Williams; Magali Labille; Amélie Laurent-Dehecq; Jean-Michel Morin; Dany Souchet (Archéologie Médiévale)
The Gien castle is a remarkably well preserved monument, located along the Loire Valley, in the middle of France. After having been subjected to numerous reuses in the past, the castle of Gien houses the patrimonial collection of the Musée national de la chasse (Hunting National Museum). Part of the castle’s history has been recently unveiled during the developer funded surveys and excavations carried out between 2011 and 2015. The aim of this work is to present the investigation lead out on the reconstitution of the inhabited areas of the Gien promontory from the 9th to the 11th century, in light of the recent archaeological discoveries. The multi-criteria approach implemented here allows us to characterise this settlement through a questioning of the observed habits. The way of life of the Lords of Gien at this period is described in relation to the results obtained by the analysis of pottery, animal bones and plant remnants, micromorphology of the soils, the archaeological artefacts and the ironwork rejects. This inhabited area is also compared to the known forms of other privileged sites of the same period.